Thymoquinone mediated hedgehog pathway activation and gut microbiota modulation in mouse colitis - Xixiang Huang; Tong Sun; Linxia Xu; Wei Liu; Zhi Ren; Zhenzeng Ma; Hailun Zheng; Dapeng Li; Qiangwu Wang; Xiquan Ke (Scientific Reports)
Abstract To investigate the treatment of ulcerative colitis by thymoquinone (TQ) through the Hedgehog signaling pathway and the composition of intestinal microbiota. A total of 24 male Balb/C mice were randomly divided into blank group, model group, thymoquinone low-dose group (20 mg/kg) and thymoquinone high-dose group (80 mg/kg), with 6 mice in each group. The concentrations of IL-1β, TNF-α, IL-10 and TGF-β in the supernatant of mouse serum were determined by enzyme-linked immunosorbent assay, and the expressions of Shh, Smo, Gli1, Ptch1, Atresin -1 (ZO-1) and Occludin in the mouse colon were detected by RT-qPCR, Western blot and immunohistochemistry. RNA-seq was used to detect changes in the intestinal microbial community of the four groups at the same time. TQ slowed down body weight, reduced disease activity index, promoted the expression of Shh, Smo, Gli1, Ptch1, Zo-1 and Occuldin in the colon, and increased the phylum levels of Bacteroidota, Campylobacterota, Desulfobacterota, Verrucomicrobiota, Deferribacterota and the abundances of Bacteroidaceae, Muribaculaceae, Akkermansiaceae, Deferrribacteraceae, Staphylococcaceae at the family level, absent from the abundance of Proteobacteria at the phylum level and Enterobacteriaceae at the family level, and inhibited the expression of IL-1β, TNF-α and TGF-β in peripheral blood, and promoted the expression of IL-10 in peripheral blood. Thymoquinone may play a role in the treatment of ulcerative colitis by upregulating Hedgehog and influencing the composition of gut microbiota.